Penerapan Convolutional Neural Network (CNN) Untuk Klasifikasi Penggunaan Masker - Rifdah Rofifah Faruk Abdullah; Maryam Hasan (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2022)
ABSTRACT RIFDAH ROFIFAH FARUK ABDULLAH. T3117114. APPLICATION OF CONVOLUTIONAL NEURAL NETWORK FOR MASK USE CLASSIFICATION The use of masks is a part of the comprehensive series of prevention and control measures that can limit the spread of certain respiratory viral diseases. Masks can be used both to protect healthy people (worn to protect themselves when in contact with an infected person) and to control the sources of prevention (to be worn by an infected person to prevent further transmission). The problem that often occurs is that many people use masks, but improperly or inappropriately. For instance, the right thing, someone uses a mask to cover the mouth and nostrils. Therefore, an application for the use of computer-assisted mask detection is made. It can detect the use of a person's mask so that the right and wrong use categories are obtained that represent it by capturing it in an image. It is done by using the Convolutional Neural Network method. In the classification stage, the accuracy results are 60- 70%. Keywords: classification, masks use, Convolutional Neural Network